Effect of Barium Titanate on the Thermal, Morphology, Surface, and Mechanical Properties of the Thermoplastic Polyurethane/Barium Titanate Composites - KAHRAMAN, MEMET VEZİR; MADAKBAŞ, SEYFULLAH (TAYLOR & FRANCIS INC, 2016)
The aim of this study was to improve thermal stability, mechanical, and surface properties of thermoplastic polyurethane (TPU) with the addition of BaTiO3. The TPU/BaTiO3 composites having various ratios of TPU and BaTiO3 were prepared. The chemical structure of the prepared composites was investigated by FTIR. Thermal stability of the samples were evaluated by thermogravimetric analysis and differential scanning calorimetry. Mechanical properties of the samples were characterized with stress-strain test. Hydrophobicity of the samples was determined by the contact angle measurements. Moreover, the surface morphology of the samples was investigated by a scanning electron microscopy. [GRAPHICS] .
Keywords: Barium titanate; composites; thermoplastic polyurethane; ELASTOMERS; MICA